The effect of second language acquisition on central auditory processing abilities and its interaction with HIV - Kambhampaty, Abby; Niemczak, Christopher E.; Leigh, Samantha M.; Lichtenstein, Jonathan; Adhikari, Monika; Fellows, Abigail M.; Magohe, Albert; Gui, Jiang; Zhang, Linda; Massawe, Enica R.; Buckey, Jay C. (Frontiers in Language Sciences, 2024)
Second language learning is a multifaceted task that offers benefits across numerous neurocognitive domains including central auditory processing. Existing cross-sectional and longitudinal data show that performance on tests of central auditory processing (central auditory tests (CATs)) worsens with HIV infection. Second language learning may modify this relationship. To explore the relationship between second language learning, central auditory processing, and its interaction with HIV, we assessed the effect of learning English as a second language on CATs among children both living with and without HIV (CLWH/CLWOH) in Dar es Salaam, Tanzania. 372 native Kiswahili speaking children aged three to ten years old (196 CLWOH, 176 CLWH) were enrolled. Participants completed questionnaires about English language learning, socioeconomic status (SES), and health history. Three central auditory teststhe Triple Digit Test (TDT), the Staggered Spondaic Word Test (SSW), and the Hearing-In-Noise Test (HINT)-were used to assess each participant's central auditory processing abilities. Multivariate linear regression was used to assess the effect of written and spoken English language learning at home and in school on CATs with age, HIV-status, and SES included in each model. HIV status, age, and SES were all significant predictors of all three central auditory tests, with CLWH performing significantly worse on all three CATs than CLWOH. Children actively learning spoken and written English at home had significantly better central auditory processing abilities on the TDT compared to children not actively learning English at home (p<0.01) independent of HIV status, age, and SES. Children learning spoken and written English at school performed significantly better on the HINT (p<0.05) than those not actively learning English at school. Learning English at home and learning English in school were associated with improved central auditory performance independent of HIV status, SES, and age. These findings also underscore the significance of second language acquisition as a potential mechanism of improving central auditory function within a Kiswahili-speaking cohort. This study found differences in central auditory processing between children exposed to English at home and in school, suggesting differences in language learning in both settings mediated by SES, and this benefit exists regardless of HIV status.